DEATH, A SURREPTITIOUS FRIENDSHIP: mortality and the impossibility of dying inbatailleand blanchot. Issue 6 (1st November 2020) - Taylor, Dan
Abstract: This article explores the friendship of Maurice Blanchot and Georges Bataille through a close reading of their thought on death and dying. An intellectual and personal friendship, both conceived of death as an "impossible" space and "limit-experience" that not only constituted human subjectivity, but could also puncture it, leading to joy through deindividuation. This could only occur indirectly – for Bataille, via the sacrifice, eroticism, drunkenness or laughter – and for Blanchot, via literature. This line of thinking leads to varying formulations of sovereignty at odds with the prosaic world of use-value. Proceeding first through their friendship, this paper then explores this thinking death through the contexts of French Hegelianism, Kojève and Heidegger. While holding much similar, the paper argues that Bataille's transgressive, embodied and deindividuating visions of death present a form of community that was overlooked by Blanchot subsequently, with consequences for theories of community and collective power today.